2021
DOI: 10.36444/nsmc.v4i2.158
|View full text |Cite
|
Sign up to set email alerts
|

The use of CONOX as a guide to the general anesthesia on laparotomy patients compared with standard clinical care– A pilot study

Abstract: Background: Avoiding excessive doses of anesthesia was fundamental, mainly to reduce the adverse effect of anesthesia. Electroencephalography (EEG)-based monitors can be used to measure the depth level of anesthesia and guide intraoperative hypnosis drug and opioid administration. This study aims to evaluate the benefit of using CONOX monitor when administering anesthesia drugs in laparotomy procedures. Method: Twenty patients aged 18-65 years with physical status ASA I-III who underwent major laparotomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…Melia et al, found that the qCON was able to predict LOC such as loss of verbal command and eyelash reflex while the qNOX was able to better predict response to noxious stimulation such as LMA insertion performed in a study and compared the qCON and qNOX indexes for the assessment of unconsciousness level and noxious stimulation response during surgery. 8 The dose of propofol was comparable (P=0.11) in CONOX and the control group found in a study done by Jehosua et al 9 In the same study, they found a significant difference (P<0.05) in the total dose of fentanyl between CONOX and control group.…”
Section: Discussionmentioning
confidence: 50%
“…Melia et al, found that the qCON was able to predict LOC such as loss of verbal command and eyelash reflex while the qNOX was able to better predict response to noxious stimulation such as LMA insertion performed in a study and compared the qCON and qNOX indexes for the assessment of unconsciousness level and noxious stimulation response during surgery. 8 The dose of propofol was comparable (P=0.11) in CONOX and the control group found in a study done by Jehosua et al 9 In the same study, they found a significant difference (P<0.05) in the total dose of fentanyl between CONOX and control group.…”
Section: Discussionmentioning
confidence: 50%
“…Цель исследования -оценка эффективности и безопасности превентивного применения различных НПВС при плановых операциях в условиях общей анестезии. Таким образом, индекс qNOX минимизирует риски, связанные с проведением общей анестезии, и позволяет оптимизировать дозировку препаратов [11].…”
unclassified